Antibacterial Activity of Moringa Leaf Layer Cake Against S. aureus and E. coli - I Ketut Budaraga; Dian Pramana Putra; Wellyalina Wellyalina (Jurnal Ilmu dan Teknologi Terapan Pertanian, 2020)
The layer cake is one of the traditional cakes that are very popular with the community. The addition of Moringa leafs is expected to extend the period of storage and the components of the nutrition can be increased. Moringa leaves indicate to contain an antibacterial compound that is the result of secondary metabolites. This compound consists of alkaloids, tannins, flavonoids, terpenoids, saponins, and others. The purpose of this study was to determine the antibacterial properties of Moringa leaves added to layer cake against pathogenic bacteria S. aureus and E. coli. Research has been implemented on April - May 2019. The testing of antibacterial activity by using well method. The results showed that the layer cake with the addition of 4% Moringa leaves indicated the high inhibition zone on the bacteria E. coli by 10.7 mm and S. aureus by 9.7 mm when compared with the addition of 1%, 2%, and 3 % Moringa leaves. The result of bacterial pathogens that were tested in Moringa leaves showed that the bacteria E. Coli had resistance to more robust compared with S. Aureus. This is indicated by the inhibition zone of E. coli that is greater than S. aureus bacteria.